Developing a national pharmaceutical research strategy in Lebanon: opportunities to bridge the gaps and reach the goals - Marwan Akel; Aline Hajj; Hala Sacre; Rony M. Zeenny; Chadia Haddad; Pascale Salameh (Taylor & Francis Group, 2022)
Pharmaceutical research can be structured into clear national strategies that optimize patient health and foster innovation. The objectives of this document are to assess the need for a national pharmaceutical research strategy based on the current situation in Lebanon, to identify the strengths and weaknesses of pharmaceutical research in Lebanon, and to suggest a pharmaceutical research strategy for Lebanon, including goals and objectives. In Lebanon, in the absence of a national health research policy, pharmaceutical research is conducted in academia or hospitals, although projects are the result of personal or team initiatives that should be organized to better serve the needs of the country. Many strengths of pharmaceutical research were identified, such as the pharmaceutical workforce and academics who are willing to contribute to research, while the implementation of the national pharmaceutical strategy represents an important opportunity to promote research. Among the weaknesses is the lack of research culture in some institutions and interinstitutional/interprofessional collaborations. Thus, the suggested strategy aims to structure pharmaceutical research in Lebanon, including the priorities towards which research is directed, the process by which research is conducted, and the workforce conducting research. It will mainly rely on the World Health Organization's interrelated goals (organization, priorities, capacity, standards, and translation). The implementation of the suggested pharmaceutical research strategy will only be achieved through the leadership of the pharmaceutical authorities and the collaboration of stakeholders.